Neuroanatomical correlates of macrostructural receptive abilities in narrative discourse in unilateral left hemisphere stroke: A behavioural and voxel‐based morphometry study. Issue 3 (30th November 2022) - Townsend, Sabrine Amaral Martins; Marcotte, Karine; Brisebois, Amelie; Smidarle, Anderson Dick; Schneider, Fernanda; Loureiro, Fernanda; Soder, Ricardo Bernardi; Franco, Alexandre da Rosa; Marrone, Luiz Carlos Porcello; Hübner, Lilian Cristine
Abstract: Background: Little is known about story retelling and comprehension abilities in groups with lower levels of education and socio‐economic status (SES). A growing body of evidence suggests the role of an extended network supporting narrative comprehension, but few studies have been conducted in clinical populations, even less in developing countries. Aims: To extend our knowledge of the impact of a stroke on macrostructural aspects of discourse processes, namely main and complementary information, in individuals with middle‐low to low SES and low levels of education. Relationships were tested between the performance in story retell and comprehension and reading and writing habits (RWH). Also, the associations between retelling and comprehension measures and their structural grey matter (GM) correlates were explored. Methods & Procedures: A total of 17 adults with unilateral left hemisphere (LH) chronic ischaemic stroke without the presence of significant aphasia and 10 matched (age, education and SES) healthy controls (HC) participated in the study. Retell and comprehension tasks were performed after listening or reading narrative stories. Voxel‐based morphometry (VBM) analysis was conducted on a subgroup of nine individuals with LH stroke and the 10 matched controls using structural magnetic resonance imaging (MRI). Outcomes & Results: Retelling and comprehension abilities were not significantly different between LH and HC, nonetheless quantitively lower in LH. Exploratory correlations showed that retelling and comprehension abilities in both written and auditory modalities were correlated with naming abilities. At the neural level, written comprehension positively correlated with GM density of the LH, including areas in the temporal pole, superior and middle temporal gyrus as well as the orbitofrontal cortex, precentral and postcentral gyri. Auditory narrative comprehension was associated with GM density of the lingual gyrus in the right hemisphere. Conclusions & Implications: The present results suggest that retelling and comprehension of auditory and written narratives are relatively well‐preserved in individuals with a LH stroke without significant aphasia, but poorer than in HC. The findings replicate previous studies conducted in groups with higher levels of education and SES both at the behavioural and neural levels. Considering that naming seems to be associated with narrative retell and comprehension in individuals with lower SES and education, this research provides evidence on the importance of pursuing further studies including larger samples with and without aphasia as well as with various SES and education levels. WHAT THIS PAPER ADDS: What is already known on this subject: Story retell and comprehension of auditory and written discourse have been shown to be affected after stroke, but most studies have been conducted on individuals with middle to high SES and high educational levels. What this paper adds to existing knowledge: The study reports on narrative retell and comprehension in both auditory and written modalities in groups of HC and individuals with LH brain damage, with low‐to‐middle SES and lower levels of education. What are the potential or actual clinical implications of this work?: This study highlights the importance of taking into consideration the sociodemographic and RWH of patients when assessing discourse retell and comprehension in both auditory and written modalities. It also underlines the importance of including patients without significant aphasia following LH stroke to look at the effect of both stroke and aphasia on narrative comprehension and story retelling.